Further characterization of Shigella-specific (memory) B cells induced in healthy volunteer recipients of SF2a-TT15, a Shigella flexneri 2a synthetic glycan-based vaccine candidate - Toapanta, Franklin R.; Hu, Jingping; Meron-Sudai, Shiri; Mulard, Laurence A.; Phalipon, Armelle; Cohen, Dani; Sztein, Marcelo B. (Frontiers in Immunology, 2023)
Shigellosis is common worldwide, and it causes significant morbidity and mortality mainly in young children in low- and middle- income countries. To date, there are not broadly available licensed Shigella vaccines. A novel type of conjugate vaccine candidate, SF2a-TT15, was developed against S. flexneri serotype 2a (SF2a). SF2a-TT15 is composed of a synthetic 15mer oligosaccharide, designed to act as a functional mimic of the SF2a O-antigen and covalently linked to tetanus toxoid (TT). SF2a-TT15 was recently shown to be safe and immunogenic in a Phase 1 clinical trial, inducing specific memory B cells and sustained antibody response up to three years after the last injection. In this manuscript, we advance the study of B cell responses to parenteral administration of SF2a-TT15 to identify SF2a LPS-specific B cells (SF2a+ B cells) using fluorescently labeled bacteria. SF2a+ B cells were identified mainly within class-switched B cells (SwB cells) in volunteers vaccinated with SF2a-TT15 adjuvanted or not with aluminium hydroxide (alum), but not in placebo recipients. These cells expressed high levels of CXCR3 and low levels of CD21 suggesting an activated phenotype likely to represent the recently described effector memory B cells. IgG SF2a+ SwB cells were more abundant than IgA SF2a + SwB cells. SF2a+ B cells were also identified in polyclonally stimulated B cells (antibody secreting cells (ASC)-transformed). SF2a+ ASC-SwB cells largely maintained the activated phenotype (CXCR3 high, CD21 low). They expressed high levels of CD71 and integrin α4β7, suggesting a high proliferation rate and ability to migrate to gut associated lymphoid tissues. Finally, ELISpot analysis showed that ASC produced anti-SF2a LPS IgG and IgA antibodies. In summary, this methodology confirms the ability of SF2a-TT15 to induce long-lived memory B cells, initially identified by ELISpots, which remain identifiable in blood up to 140 days following vaccination. Our findings expand and complement the memory B cell data previously reported in the Phase 1 trial and provide detailed information on the immunophenotypic characteristics of these cells. Moreover, this methodology opens the door to future studies at the single-cell level to better characterize the development of B cell immunity to Shigella.